Role for ribosome-associated complex and stress-seventy subfamily B (RAC-Ssb) in integral membrane protein translation - Acosta-Sampson, Ligia; Döring, Kristina; Bukau, Bernd; Kramer, Günter (The journal of biological chemistry, 2017)
Targeting of most integral membrane proteins to the endoplasmic reticulum is controlled by the signal recognition particle, which recognizes a hydrophobic signal sequence near the protein N terminus. Proper folding of these proteins is monitored by the unfolded protein response and involves protein degradation pathways to ensure quality control. Here, we identify a new pathway for quality control of major facilitator superfamily transporters that occurs before the first transmembrane helix, the signal sequence recognized by the signal recognition particle, is made by the ribosome. Increased rates of translation elongation of the N-terminal sequence of these integral membrane proteins can divert the nascent protein chains to the ribosome-associated complex and stress-seventy subfamily B chaperones. We also show that quality control of integral membrane proteins by ribosome-associated complex-stress-seventy subfamily B couples translation rate to the unfolded protein response, which has implications for understanding mechanisms underlying human disease and protein production in biotechnology.